2005
DOI: 10.1209/epl/i2005-10063-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the spin-orbit coupling in the dissociation dynamics of rare-gas ionic trimers

Abstract: A dynamical model combining an extended diatomics-in-molecules approach with the inclusion of the spin-orbit coupling and the mean-field dynamics method has been developed for rare-gas cluster cations, Rg + n , and employed in simulations of the photodissociation dynamics of argon, krypton, and xenon singly charged trimers. As the first step, total kinetic energies deposited in the photofragments are calculated for all the three rare gases and for a wide range of photon energies, and compared with available ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
5
12
0
Order By: Relevance
“…In this case, only monomers are produced in experiments [16] with a bimodal kinetic energy distribution (fast and slow fragments) both for neutrals and for ions. Our earlier [6,13,[17][18][19][20] as well as recent [14,15] theoretical simulations have nicely reproduced these experimental findings and showed that, in visible excitation, the trimer, initially almost linear and symmetric, mainly explodes leaving the central atom to rest in the center-of-mass. Interestingly, for the higher photon energies, the ions are produced in the high fine-structure state [15] corroborating the experimental findings [16].…”
Section: Introductionsupporting
confidence: 68%
See 4 more Smart Citations
“…In this case, only monomers are produced in experiments [16] with a bimodal kinetic energy distribution (fast and slow fragments) both for neutrals and for ions. Our earlier [6,13,[17][18][19][20] as well as recent [14,15] theoretical simulations have nicely reproduced these experimental findings and showed that, in visible excitation, the trimer, initially almost linear and symmetric, mainly explodes leaving the central atom to rest in the center-of-mass. Interestingly, for the higher photon energies, the ions are produced in the high fine-structure state [15] corroborating the experimental findings [16].…”
Section: Introductionsupporting
confidence: 68%
“…Our earlier [6,13,[17][18][19][20] as well as recent [14,15] theoretical simulations have nicely reproduced these experimental findings and showed that, in visible excitation, the trimer, initially almost linear and symmetric, mainly explodes leaving the central atom to rest in the center-of-mass. Interestingly, for the higher photon energies, the ions are produced in the high fine-structure state [15] corroborating the experimental findings [16]. It should be noticed that, in a very recent experiment on Ar + 2 and Ar + 3 [8], the velocity vectors of all fragments have been collected in coincidence thanks to the development of sophisticated multicoincidence techniques.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations